2015
DOI: 10.1002/dc.23322
|View full text |Cite
|
Sign up to set email alerts
|

Identification of intranuclear inclusions is useful for the cytological diagnosis of ovarian clear cell carcinoma

Abstract: The identification of intranuclear inclusions, in particular a high frequency and multiple intranuclear inclusions in a single nucleus, is useful for the cytological diagnosis of CCC. Furthermore, these results may be applicable to ascites cytology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Currently, the frequency of NGs and ICIs in renal cell carcinoma histological specimens is 96 and 65%, respectively ( 18 ). In contrast, the frequency of ICIs in cytological specimens of ovarian cancer is 38% ( 19 ), while the frequency of ICIs in cytological specimens of thyroid papillary carcinoma cases is 88.9% ( 20 ). In terms of lung adenocarcinoma cases, Choi et al reported the frequency of either NGs or ICIs in anaplastic lymphoma kinase (ALK)-positive cases and ALK-negative cases as 21.1 and 9.9%, respectively ( 21 ).…”
Section: Discussionmentioning
confidence: 89%
“…Currently, the frequency of NGs and ICIs in renal cell carcinoma histological specimens is 96 and 65%, respectively ( 18 ). In contrast, the frequency of ICIs in cytological specimens of ovarian cancer is 38% ( 19 ), while the frequency of ICIs in cytological specimens of thyroid papillary carcinoma cases is 88.9% ( 20 ). In terms of lung adenocarcinoma cases, Choi et al reported the frequency of either NGs or ICIs in anaplastic lymphoma kinase (ALK)-positive cases and ALK-negative cases as 21.1 and 9.9%, respectively ( 21 ).…”
Section: Discussionmentioning
confidence: 89%
“…Nuclear pleomorphism is moderate, and nucleoli are frequently present. Intranuclear inclusions may be seen [69], as well as the presence of an extracellular hyalinized matrix, corresponding to stromal hyalinization often seen in histologic sections and cell blocks (Fig. 14) [70].…”
Section: Seromucinous Neoplasmsmentioning
confidence: 99%
“…This matrix is composed of basement material, mostly collagen IV and laminin, and can be seen in a circumferential pattern where the stroma is centrally located in a spherule-like formation ("raspberry body" or "mirror ball"), or as a large globule-like extracellular material [71]. Rare psammoma bodies can also be present [69,70].…”
Section: Seromucinous Neoplasmsmentioning
confidence: 99%
“…Intranuclear inclusions are important diagnostic features in many benign and malignant neoplasms, such as adrenal cortical adenoma, thyroid papillary carcinoma, melanoma, meningioma, hepatocellular carcinoma, pancreatoblastoma, pulmonary blastoma and fetal-type adenocarcinoma, and lobular breast carcinoma [15] as well as recently reported ovarian serous carcinoma [2]. In renal epithelial cell tumors, the present of intranuclear inclusions has been reported in all three major subtypes, including chromophobe, papillary and ccRCC [35].…”
Section: Introductionmentioning
confidence: 99%